Rhetorical structure, cyclical patterns and stance markers in forestry research articles - Nasirizadeh, Zahra (2021)
There has been a surging interest in the study of genre-based analysis of the research article (RA) since three decades ago. Over these years, English for Academic Purposes (EAP) writing research has highlighted the intricacy and evolving nature of discursive practices by underlining writers’ communicative goals and linguistic choices, in addition to the expectations of discourse community members. Some practitioners, typically novice writers, are unaware of the critical role that rhetorical structure and linguistic features serve in creating a research article (RA) acceptable to the respective discourse communities. Therefore, it seems essential to perform analysis at both macro (rhetorical structure) and micro levels (linguistic features) as it provides useful information crucial to prepare apt pedagogical materials for novice writers to compose comprehensive research articles. Genre descriptions of research articles vary in their focus from the selected sections to the whole article. Very limited studies have investigated the overall organisational structure of articles with all the main sections of Introductions-Methods-Results-Discussion (IMRD). The current study set out to a) analyse the rhetorical structure of IMRD sections of forestry research articles, b) analyse the cyclical move patterns recurring in each IMRD section and c) examine stance markers realised in each move in the respective sections. Mixed methods of quantitative and qualitative were applied in this study. A corpus of 40 research articles from 5 ISI journals was selected for this study. The selected articles were extracted from high impact factor journals in forestry. The corpus was analysed based on Kanoksilapatham’s (2005) model as the analytical tool to explore the rhetorical structure and cyclical patterns of IMRD sections. As to the linguistic features, this thesis applied Hyland’ (2005) interactional model of metadiscourse to study stance markers of moves in the overall IMRD sections. On the basis of results from the analysis of rhetorical structure of RAs, some new moves and steps were realised in each respective section, owing to the specilised nature of forestry discipline, as an applied hard science. In this regard, the highest number of new moves or steps was registered in Introductions, with the Results sections remaining unchanged. As to the cyclical patterns, the findings pointed to the pervasiveness of particular function-oriented cycles and sequences in each IMRD section. In Introductions, the Move1-Move2 cycle, in Methods the Move 4-Move 5, in Results the Move 11-Move 12, and in Discussions the Move 13-Move 14 cycles were the most frequent cyclical patterns. Exploring stance markers, each move was found to be characterised with particular epistemological stance markers in cases attributable to the nature of forestry discipline and the communicative purpose of each move. Overall, hedging devices and self-mentions were found to be the most prototypical stance markers, with boosters and attitude markers as the least indexed ones in the corpus. To conclude, findings from the present study further testify to the integral role of RAs genre knowledge in EAP realm. Raising novice writers’ awareness of the prototypical principles behind rhetorical structure and linguistic features of RAs in a specific discipline could be considered the main potential pedagogical benefit of genre analysis approach.